PSEUDOBULBAR AFFECT AND COGNITIVE DECLINE POST SEVERE TRAUMATIC BRAIN INJURY: A CASE REPORT - Yusari, I Gusti Agung Ayu Andra; Laksmidewi, Anak Agung Ayu Putri (MNJ (Malang Neurology Journal), 2024)
Introduction: Pseudobulbar affect is described as episodes of laughing or crying that occur suddenly and uncontrollably without appropriate stimulation. Pseudobulbar affect is often preceded by various neurological disorders, one of which is a history of severe head injury. Case Report: Female, 21 years old, experienced sudden frequent laughing for no apparent reason and could not be controlled. This has been happening after she suffered a severe head injury, which was a subarachnoid hemorrhage, about two years ago. She was diagnosed with pseudobulbar affect according to Cummings criteria and confirmed by Center for Neurologic Study – Lability Scale (CNS-LS) questionnaire with a score of 19. The patient also complained of forgetting things, therefore a cognitive function was examined with Indonesian Version of the Montreal Cognitive Assessment (MoCA-Ina) with a score of 14 which indicated moderate cognitive impairment. Discussion: Pseudobulbar affect post traumatic brain injury is suspected to be caused by decreased inhibition of sensory cortex transmission to the motor cortex and limbic system leading to disturbances in the cerebellum and decreased threshold for emotional expression. Pseudobulbar affect may coexist with impaired cognitive function due to the intersection of the anatomical structure of cognitive function with pathways that regulate emotion. Conclusion: Pseudobulbar affect with cognitive impairment creates a burden and interferes the patient’s quality of life. It is necessary for health workers to be able to identify the clinical manifestations of pseudobulbar affect as a complication after traumatic brain injury, therefore optimal management for the patients can be achieved.